Infiltrative laryngeal lipoma in a Yorkshire Terrier as cause of severe dyspnoea - Brunnberg, M.; Cinquoncie, S.; Burger, M.; Plog, S.; Nakladal, B. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2013)
A 10-year-old Yorkshire Terrier with suspected laryngeal paralysis was referred for further examination and surgical treatment. The dog displayed severe dyspnoea and dysphonia. Ventrolateral to the larynx a soft-elastic mass of 2 cm diameter was palpated and confirmed by radiography. Histopathological examination of the resected mass revealed an infiltrative lipoma/lipoma. Although the dog totally recovered after surgery, the prognosis remains guarded due to the high risk of a recurrence. Tumours of the larynx in general and an infiltrative lipoma specifically should be added to the list of differential diagnosis in dogs presented with clinical signs that could be misinterpreted as laryngeal paralysis.
Keywords: Laryngeal paralysis; laryngeal tumour; neoplasia